Social Media for Businesses: An Effective Social Capital Tool for Entrepreneurs - Agrawal, Romi (2017)
Social capital is very crucial for entrepreneurs. It is one of the key factors for entrepreneurial growth. Although, it is not an easy task to be an entrepreneur as their roles and responsibilities lead to the success or failure of the firm. Entrepreneurs participate with their social networks which include family, friends and further relationships made with individuals. Interacting with their social networks leads to acquiring resources for the firm and personal growth. Majority of literatures specify social capital creates and maintains trust and respect among the individuals. But it does not specify any other new ways is which entrepreneurs build social capital which is important for an entrepreneurial firm. Adding to social networks, the influence of social media on the entrepreneur’s social capital has been considered in this research which lead acquiring a better network and capital with fellow members. Thus, the aim of this research is to display the use of social media by entrepreneurs for increasing their social networks which has therefore helped in increasing their social capital for personal and entrepreneurial growth. Entrepreneurs were studies from various industries to achieve a broader knowledge in regards to their social capital.